2019
DOI: 10.1111/jcpt.13004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of regulatory action on denosumab‐induced hypocalcaemia in Japan

Abstract: What is known and Objective Since its introduction in April 2012, denosumab has been administered to approximately 7,300 patients as of August 2012, and 32 cases of serious hypocalcaemia after denosumab administration, including two deaths, have been reported in Japan. A Dear Healthcare Professional Letter of Rapid Safety Communication (‘Blue letter’) was released to warn about the risks of hypocalcaemia associated with denosumab. The goal of this study therefore was to measure the impact of regulatory action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…During the 12-mo study period, no patients experienced any fractures or moderate-to-severe adverse events. Hypocalcemia was observed in 11.7% (7 of the 60 patients) and mainly developed in the early phase after the first dosing, which was similar to results in a previous report[ 44 ]; however, it was asymptomatic, transient, and mild (grade 1). Thus, denosumab treatment was safe in CLD patients.…”
Section: Discussionsupporting
confidence: 89%
“…During the 12-mo study period, no patients experienced any fractures or moderate-to-severe adverse events. Hypocalcemia was observed in 11.7% (7 of the 60 patients) and mainly developed in the early phase after the first dosing, which was similar to results in a previous report[ 44 ]; however, it was asymptomatic, transient, and mild (grade 1). Thus, denosumab treatment was safe in CLD patients.…”
Section: Discussionsupporting
confidence: 89%
“…Fourth, we did not investigate the effect of DSCs on ADR prevention, although previous studies revealed that DSCs resulted in a change in prescriptions in Japan. DSC for denosumab‐induced hypocalcemia changed the physicians' attitudes toward the combination use of denosumab with vitamin D/calcium supplement 15 . Additionally, another study revealed that dabigatran use for patients with a specific background (i.e., elderly, renal dysfunction, receiving antiplatelet medication) was altered after the issuance of DSC for dabigatran‐induced bleeding 16 .…”
Section: Discussionmentioning
confidence: 99%
“…DSC for denosumab‐induced hypocalcemia changed the physicians' attitudes toward the combination use of denosumab with vitamin D/calcium supplement. 15 Additionally, another study revealed that dabigatran use for patients with a specific background (i.e., elderly, renal dysfunction, receiving antiplatelet medication) was altered after the issuance of DSC for dabigatran‐induced bleeding. 16 The effects of DSCs by the FDA 17 and the EMA 18 on drug use have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that, to minimize the risk for hypocalcemia, calcium (>500 mg) and vitamin D (400 IU) should be supplemented daily in patients receiving either of the BTAs. 7,45 The bone is a commonly involved site in malignant progression, either as a site of metastasis or as a feature of MM. Previous meta-analyses have shown the efficacy of denosumab mainly as intervention in bone metastases.…”
Section: Discussionmentioning
confidence: 99%